CHARACTERIZATION OF SELECTED ISOLATES OF INDIGENOUS STREPTOMYCES SPECIES AND EVALUATION OF THEIR ANTIFUNGAL ACTIVITY AGAINST SELECTED PLANT PATHOGENIC FUNGI - K, Getha; S, Vikineswary; W.H, Wong; T, Seki; A, Ward; M, Goodfellow (Malaysian Journal of Science, 2004)
Twenty-five representative isolates from a collection of 54 indigenous actinomycetes isolated from coastal resources, were evaluated for inhibition against plant pathogenic fungi in vitro. Fusarium oxysporum f.sp. cubense (Foc) race 4 and Rhizoctonia solani exhibited higher resistance to the antifungal effects of the isolates when compared to the other test fungi. Seven isolates with potential pathogen-inhibitory capabilities belonged to the gray colour class of Streptomyces. Isolate g10 with a wide and strong antifungal spectrum against a variety of pathogenic fungi belonged to the Streptomyces violaceusniger cluster. This isolate could be a potential biological control agent.